Experimental investigation on mechanical properties of HSSCC containing waste steel fibers obtained from end-of-life tires - Akça, Kutalmış Recep; İpek, Metin and Çelenk, Sevgi and Karabulak, Aykut (Revista de la Construcción. Journal of Construction, 2023)
In this study, use of end-of-life tires (ELTs) in self-consolidating concretes (SCC), which enable higher rates of fiber use than conventional concrete due to its superior flow properties, for the elimination of the environmental negative impacts and recycling of them were aimed. Besides, it is aimed to investigate the behavior of waste steel wires with different aspect ratio obtained from different types of tires, contrary to what is mostly researched in the literature. Therefore, bead, cord and base wires, obtained from tires, were used in high-strength self-consolidating concrete (HSSCC) production as fiber reinforcement. Fresh and hardened state properties of the waste wire-reinforced (1-2-3%) samples of different sizes that were produced, were compared with industrial steel-reinforced and non-fibrous samples. In this regard, slump flow and T50 durations were determined, compression and bending tests were performed. Significant improvements in the mechanical properties of conventional concretes were observed with the use of waste wire. Using the optimum ratio of waste wire, an increase of approximately 102% in flexural strength and 14% in compressive strength was observed compared to the reference specimen. Aspect ratio was recognized as one of the most effective factor on optimum fiber content. Moreover, experimental results were analyzed with "paired sample t-test", and it was seen that there were no considerable differences in the mechanical properties of the samples in which industrial fiber and waste-wire had been used. Besides, cost analysis was carried out to assess the economic benefits of the use of waste tire wires in the concrete industry.